2021
DOI: 10.29321/maj.10.000561
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Parental Lines and Land Races of Pearl Millet [Pennisetum glaucum (L) R. Br.] by DUS Descriptors

Abstract: An experiment was conducted to characterize 31 pearl millet genotypes with 28 morphological traits using DUS descriptors at the Department of Millets, Tamil Nadu Agricultural University, Coimbatore, during Kharif 2019. The landrace Kizikuppam local was found to have a very long leaf length and a medium leaf width, indicating a high leaf area index, an important physiological trait that could be employed in future breeding programmes. The genotypes PT 6067, PT 6707, PT 6710, Cumbu 1, Uthangarai local and Shoola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…A greater distance between clusters also results in a broader spectrum of variability in the segregating population used for selection. It was also found that genotypes in the same cluster or those that had low genetic divergence and relatively small statistical distances were a greater probability to yield the desired heterotic effects in the population as due to of crossing if they complement some important weaknesses of each other, as opposed to those including genotypes with wide genetic differences and falling in separate clusters (Dave and Joshi, 1995;Kalagare et al, 2022) The extent of genetic diversity between the genotypes was also determined by the substantial variability in cluster means for various characters. The cluster-specific and overall cluster-specific means for each character are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…A greater distance between clusters also results in a broader spectrum of variability in the segregating population used for selection. It was also found that genotypes in the same cluster or those that had low genetic divergence and relatively small statistical distances were a greater probability to yield the desired heterotic effects in the population as due to of crossing if they complement some important weaknesses of each other, as opposed to those including genotypes with wide genetic differences and falling in separate clusters (Dave and Joshi, 1995;Kalagare et al, 2022) The extent of genetic diversity between the genotypes was also determined by the substantial variability in cluster means for various characters. The cluster-specific and overall cluster-specific means for each character are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%